Development Possibilities of the Port of Koper - Igor Trupac; Livij Jakomin; Ratimir Dovečar (Promet - Traffic&Transportation, 1970)
The extent to which Slovenia will exploit its good geographictransport position, whether it will be merely a transportcorridor or assume an additional quality (e.g. a distributioncentre or a logistic centre) will depend on a cluster of circumstances.The importance will also be laid on how Slovenia willpresent itself and what it will offer to Europe and the rest of theworld. One of its best assets is the Port of Koper (favourable position,good condition, capacities) in the frame of the whole logisticsystem.A larger volume of transport and consequently be/fer exploitationof the Port of Koper will in the future depend on increasedtransit. However, to acquire new cargo, the mere installationand modernisation of port infrastructure and rise in thequality of services may not be sufficient: it will also require goodconnections to the hinterland.